Developing Halal Industry in Indonesia using Interpretive Structural Modeling (ISM) - Rusydiana, Aam Slamet; Mahsyar, Nun Maziyyah (SMART Insight, 2023)
Halal industry has become a popular object and the latest trends in the world of international business. Not only in Indonesia but also Malaysia, Thailand even Europe began to glance at the potential and opportunities for halal industry. The phenomenon that began to develop halal industry in recent years is quite the attention of businesses and consumers themselves. Labeling